(untitled) - Hartley, Bernard (London, 1992)
This book covers the elementary structures and vocabulary of English with emphasis on developing oral skills. The material consists of 80 units, each unit provides a 50-minute lesson and is clearly laid out on a separate page
Keywords: English language; Sudy and teaching